Investigation of the process of lactose enzymolysis in the production of acidophilic-whey ice cream - Mykhalevych, Artur; Sapiga, Victoria; Polishchuk, Galyna; Osmak (Fedchenko), Tetiana (My University, 2021)
The use of whey concentrates in ice cream requires taking into account the specifics of their possible impact on product quality in each case. Thus, enzymatic hydrolysis of lactose is widely used to reduce the content of milk sugar in whey of different degrees of concentration.
Keywords: ice cream; acidophilus ice cream; serum; сироватка; ацидофільне морозиво; комбіновані молочні продукти; кафедра технології молока і молочних продуктів